Mobile learning in chemistry classes - an introduction and practical tips. - Urbanger, Michael; Kometz, Andreas (Research, theory and practice in chemistry didactics. Research and research oriented studies. Proceedings of the 23rd International Conference on Chemistry Education., 2014)
Chemistry is considered a difficult subject. The reason for this is the necessary ability to abstract, in order to understand the background and sequences of chemical processes that are macroscopically invisible. This ability must first be acquired - which involves deconstructing existing, mostly incompatible knowledge structures. Media are in this context a necessary teaching aid. Teachers have to use assistance in training students how to set up understanding for chemical processes. Therefore media must be integrated as a part of lessons. It is essential to know which media are suitable and how to use them. A special approach to digital media is inevitable. With the help of a tablet or a smartphone worksheets, films, photos and instruction guides for experiments are accessible at any time. It is always available as a medium for presentations and individual performance tests can be offered, too. Every student knows how to use this media, so it is essential to implement them in a new form of teaching [the authors] call "mobile learning". The secondary school "Realschule am Europakanal" in Erlangen, Germany, has already successfully integrated tablets as part of the curriculum in all subjects. In project classes students use this medium for all learning purposes. Chemistry also benefits from this new method of open lessons, which allows students to work together, even outside of rigid class rules. (Orig.).
Keywords: Mediendidaktik; Medieneinsatz; Medienpädagogik; Lerntheorie; Experiment; Computerunterstützter Unterricht; Unterricht; Fachdidaktik; Chemieunterricht; Mobil-Telefon; Smartphone; Tablet PC